Kandungan Hukum Islam Dalam Ayat-Ayat Mutasyabihat - Ruslan Ruslan (Fakultas Syariah UIN Antasari, 2022)
Abstract: The study of mutasyabihat verses in relation to Islamic law looks rather unusual. This is because the assumption built by the scholars is